Germination of Spotted Spurge (Chamaesyce maculata) Seeds in Response to Different Environmental Factors. Issue 2 (June 2015) - Asgarpour, Rayhaneh; Ghorbani, Reza; Khajeh-Hosseini, Mohammad; Mohammadvand, Elmira; Chauhan, Bhagirath Singh
Abstract : Spotted spurge, a C4 species, is a summer annual weed, introduced to the Golestan province of Iran in 2006. A series of laboratory experiments were conducted at the Faculty of Agriculture, Ferdowsi University of Mashhad, Iran, to evaluate the influence of environmental factors on seed germination of spotted spurge. Seeds germinated over a constant temperature range of 25 to 45 C with a 14-h photoperiod and at 30 to 50 C in continuous darkness. Seeds germinated at alternating day/night temperature regimes of 25/15 to 45/35 C, with maximum germination (> 80%) at alternating day/night temperatures of 35/25, 40/30, and 45/35C. Germination increased from 23.5 to 98% as water potential increased from −0.6 to 0 MPa (control). Germination was > 85% at sodium chloride (NaCl) concentrations up to 80 mM, with no germination at 160 mM NaCl. Germination was not affected by pH, and it was > more than 95% at pH ranging from 4 to 9. The germination of seeds submerged in water for a period less than 3 wk was > 60%, whereas no germination was observed after 9 wk of submergence in water. The results of our study could help to develop effective management strategies for this species. The results also suggest that spotted spurge could invade most tropical regions of Iran.